2019
DOI: 10.3390/ijerph16214246
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Groundwater Quality and Human Health Risk (HHR) Evaluation of Nitrate in the Central-Western Guanzhong Basin, China

Abstract: To investigate the quality of domestic groundwater and assess its risk to inhabitants of the Guanzhong Basin, China, 191 groundwater samples were collected to analyze major ions, nitrate, pH, total dissolved solids (TDS), total hardness (TH), and electrical conductivity (EC). The physiochemical parameters, hydrochemical facies, and sources of major ions were analyzed using Durov diagrams, bivariate diagrams, and chloro-alkaline indices (CAI-I and CAI-II). The suitability of groundwater for drinking, the nitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Heavy metals contamination is posing a major problem to the aquatic environment and, therefore, are hazardous towards living beings [4,5]. Many prior studies concluded that there is an adverse health effect related to heavy metals exposure [6,7]. Water quality for the designated purpose is a function of water parameters concentration value with their desirable and permissible limits as per national and world health organization standards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals contamination is posing a major problem to the aquatic environment and, therefore, are hazardous towards living beings [4,5]. Many prior studies concluded that there is an adverse health effect related to heavy metals exposure [6,7]. Water quality for the designated purpose is a function of water parameters concentration value with their desirable and permissible limits as per national and world health organization standards.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the expression of MI and PoS are given in Equations (5) and (7). The influence of the sub-index for each heavy metal will be added to the overall index even when M i is less than MAC, leading to an erroneous increase of MI and PoS.…”
mentioning
confidence: 99%
“…As per WHO 2011 standard, few water samples exceed the limit for drinking during January and June. Higher EC content in the samples endorses the enrichment of salts in the groundwater (Zhang et al 2019). In the study area, the TDS value ranged from 60 to 1294 mg/l during January and varied from 53 to 1384 mg/l during June (Fig.…”
Section: Drinking Water Qualitymentioning
confidence: 76%
“…With the rapid development of the social economy, the natural environment is constantly being polluted by humans [ 1 , 2 , 3 ]. Groundwater is an important resource for human survival, and it is also an important consumable for industrial development such as coal mining in the arid and semi-arid regions of Northwest China [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coal seams in northern China mainly exist in the Jurassic strata, which contains several aquifers [ 3 , 18 , 19 ]. The mining of these coal seams will affect the quantity and quality of groundwater in the overlying aquifer, increase the circulation of groundwater, and cause water inrush and water pollution [ 20 ].…”
Section: Introductionmentioning
confidence: 99%